2011
DOI: 10.1176/appi.ap.35.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Importance of Professional Behaviors Among Medical Students, Residents, and Attending Physicians

Abstract: All three groups surveyed rated the majority of items as Important or Very Important, indicating that they value professional behavior. Resident physicians had the highest mean score in every category measured. Overall, medical students rated most items related to professionalism as less important than the two other groups surveyed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 7 publications
2
20
1
Order By: Relevance
“…Majority of students Govindaraja C, Ramachandran G, Ko Ko Min A MedEdPublish https://doi.org/10.15694/mep.2016.000097 in both years preferred learning professionalism by role modeling by teachers as the first choice followed by case studies, lecturers and movies which is in line with the findings of prior research (Akhund et al, 2014;Byszewski et al, 2012;S. R. Cruess et al, 2008;Morreale, Balon, & Arfken, 2011;Ratanawongsa et al, 2006;Riley & Kumar, 2012;Weissmann, Branch, Gracey, Haidet, & Frankel, 2006). Students imbibe professional values from the culture of the learning environment, (Mann, 2011) the teachers, peers and hospital patients to practice in the community, evolving with time, in their professional journey (Johnston, 2006).…”
Section: Higher Integrity Displayed By Staff Than Medical Studentssupporting
confidence: 85%
“…Majority of students Govindaraja C, Ramachandran G, Ko Ko Min A MedEdPublish https://doi.org/10.15694/mep.2016.000097 in both years preferred learning professionalism by role modeling by teachers as the first choice followed by case studies, lecturers and movies which is in line with the findings of prior research (Akhund et al, 2014;Byszewski et al, 2012;S. R. Cruess et al, 2008;Morreale, Balon, & Arfken, 2011;Ratanawongsa et al, 2006;Riley & Kumar, 2012;Weissmann, Branch, Gracey, Haidet, & Frankel, 2006). Students imbibe professional values from the culture of the learning environment, (Mann, 2011) the teachers, peers and hospital patients to practice in the community, evolving with time, in their professional journey (Johnston, 2006).…”
Section: Higher Integrity Displayed By Staff Than Medical Studentssupporting
confidence: 85%
“…Mary Morreale conducted a study in 2011, and reported that resident physician's mean scores were highest for each professionalism category when compared to medical students indicating the value of professional behavior (Morreale MK et al 2011). In our study, almost similar results were produced showing more importance to professional behavior by faculty members when compared to medical students (Phillips SP & Clarke M. 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cross sectional study was designed. We have used validated questionnaire regarding attitudes towards professionalism, utilized in previous studies (Morreale MK et al 2011). Author's permission to use questionnaire was taken prior to its use.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings indicate that irrespective of place of high school education, all Pakistani and Pakistani heritage students have rated aspects of professional behavior as equally important for a medical doctor. There is currently a wealth of evidence from the west that highlights the importance of professionalism from the students’ viewpoint [34-36]. …”
Section: Discussionmentioning
confidence: 99%